Penile disassembly technique by Perovic for epispadias repair - Dina Manasherova; German Kozyrev; Sergei Yatsik; Rados Djinovic (Urology Video Journal, 2022)
Introduction: Bladder exstrophy remains one of the most challenging and complex congenital conditions in pediatric urology. Various techniques have been described to reconstruct penile anatomy, yet a high risk of complications remains [1-5]. There is a limited number of articles dedicated to the use of penile disassembly technique by Perovic.In the presented video, our objective was to demonstrate the improved penile disassembly by Perovic technique. Material and methods: A 23-year-old male patient presented to the clinic after 5 unsuccessful penile surgeries with dorsal penile curvature and meatus located dorsally. With a circumferential incision along the coronal edge full degloving is performed, and urethral plate is mobilized. Cavernous bodies and neuro-vascular bundles are mobilized. One of the cavernous bodies is detached from the glans. Urethral plate is tubularized until the tip of the glans and deepened below the cavernous bodies. An artificial erection test is performed that shows dorsal curvature. Cavernous bodies are rotated inwards and sutured together to correct curvature. Another artificial erection test is performed which demonstrated a straight penis. Integrity of neuro-vascular bundles is restored, and correct anatomy is reconstructed. Peno-scrotal and peno-pubic junctions are formed. Penile skin is sutured and reconstructed. At the end of the surgery, umbilicoplasty is performed with rectangular skin flap. The results of the surgery were analyzed in both early- and long-term follow-up of up to 3 years. Results: In early and 3-year follow-up, the patient had successful results of the treatment – no recurrent penile curvature was recorded, cosmetic result was close to natural, and no edema was present. Some scarring remained due to the high number of previous surgeries. Conclusions: The improved penile disassembly technique by Perovic allows to get successful both cosmetic and functional results, reconstructing penile anatomy, and decrease the number of post-operative complications preventing recurrence of penile curvature.